Retrieval agent for floral nursery / Normaizura Nor - Nor, Normaizura (2005)
Information Retrieval agent has been developed in many t5^es of applications such as Internet search engine and others. This project is all about implementing the Information Retrieval agent for floral nursery implementation. There are two problem occurs in this project. The problems are waste time and lack of information. The first objective in this project is to identify the criteria for the customers to buy the flowers. The second objective of this project is to suggest the nursery according to the criteria chosen by the customers. The suggestion is given according to the customer's requirement. The scope of this project based on the criteria. The criteria involved are the types of flowers sold in the nursery, the costs or price of the flowers and the location of the nursery according to the state and city. This project is designed to be robust and reliable. The methodology of this project is project definition, literature search and survey, data collection, project design and project constructing. The Information Retrieval agent will produce the suggestion according to the criteria chosen by the customers. The enhanced of this Information Retrieval agent will present better results and fulfill all customers' requirement. This project help in reducing the waste time and get the information needed on that time. The weaknesses of this project are the function in this project can be added to improve the ability and the types of flowers to limited.